1989
DOI: 10.3109/00207458909002162
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychology of de Novo Patients with Idiopathic Parkinson's Disease: The Effects of Age of Onset

Abstract: One hundred de novo patients with Parkinson's disease (PD) were classified into two groups according to age of onset of symptoms. Seventy two patients were under 70 years and 28 were 70 years and over. All patients were given neurological and neuropsychological assessments, and the severity of the signs was rated on a modified Columbia scale. The neuropsychological assessment was also administered to 50 age-and-education-matched controls. The neuropsychological test battery included tests of verbal learning, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 34 publications
2
49
1
Order By: Relevance
“…Frontal lobe dysfunction in PD dementia has been documented in many clinical studies, although both the clinical signs and degree of atrophy differ significantly from that occurring in the frontotemporal degenerative dementias [34,35], Frontal deficits in PD are often more marked in older patients [4,25,36], and mild or absent in nondemented PD patients [1,37], The mild frontal lobe atrophy noted in our late-onset PD cases may be the ana tomical substrate for such a difference. The late-onset PD cases had significant cortical plaque pathology compared with controls and middle-age-onset cases but were with out cortical neuronal pathology.…”
Section: Climcopathological Correlationsmentioning
confidence: 89%
See 2 more Smart Citations
“…Frontal lobe dysfunction in PD dementia has been documented in many clinical studies, although both the clinical signs and degree of atrophy differ significantly from that occurring in the frontotemporal degenerative dementias [34,35], Frontal deficits in PD are often more marked in older patients [4,25,36], and mild or absent in nondemented PD patients [1,37], The mild frontal lobe atrophy noted in our late-onset PD cases may be the ana tomical substrate for such a difference. The late-onset PD cases had significant cortical plaque pathology compared with controls and middle-age-onset cases but were with out cortical neuronal pathology.…”
Section: Climcopathological Correlationsmentioning
confidence: 89%
“…The size of this volume loss therefore may be underestimated when the cross-sectional area of one or a few slices are measured [30,40], Hippocampal loss associ ated with memory impairment has been demonstrated in nondemented aged patients [43], In addition, all patients with PD are impaired in spatial working memory, regard less of medication or the presence or absence of dementia [44], These observations suggest that a reduced hippo campal volume may contribute to memory dysfunction. A reduced performance in tasks requiring verbal memory or visuospatial, sequencing and temporal ordering skills arc also characteristic of PD [4,5,8,25,[45][46][47][48]. These defi cits appear to be common to all parkinsonian groups and may also be associated with the loss of hippocampal vol ume.…”
Section: Climcopathological Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies dealing with the relationship of cognitive dysfunction and other disease characteristics in non demented patients with Parkinson's disease (PD) found a rather scattered pattern of associations between single test performance and motor symptoms [39,42,46]. This pattern may result from the fact that these studies aimed at a large variety of tests in order to cover a great diversity of cognitive functions and also from the heterogeneity of the patients under study.…”
Section: Introductionmentioning
confidence: 99%
“…Reassessment after 3 years showed that no significant improvement in neuropsychological test scores resulted from treatment with levodopa or bromocriptine [3]. These results suggest that replacement of DA does not improve cognitive functioning despite improving the mo tor symptoms of PD.…”
Section: Introductionmentioning
confidence: 58%